Community awareness of ecological benefits of mangrove forest in Sibuti, Sarawak, Malaysia - Shah, Kaleem (2015)
Mangrove forest is highly productive and plays an important role to the coastal ecosystem functions including livelihoods of the adjacent coastal communities. Like other ecosystems, mangrove provides enormous tangible and intangible benefits to both the local communities and ecology. Millions of people are dependent on mangroves for their livelihoods around the world including Malaysia. Malaysia is gifted with numerous natural resources and nearly 580,000 ha of mangrove forests grow scattered countrywide, whereas, the state of Sarawak contributes 26% to the total. Many researchers in Malaysia have been focused on ecological and environmental aspects of mangroves; however very few research work are documented on social linkage aspect to this unique characteristic of forest particularly in Sarawak. Hence, this study was focused on the mangroves and its benefits to the local community and their awareness level with regard to the mangrove forest of Sibuti, Sarawak. Ethnoecological approach was adopted during the study. For social aspect, data was recorded from 60 respondents using simple random sampling techniques in three villages surrounding Sibuti mangrove forest through structured and semi-structured interview schedule. While, field survey was conducted through transect line method for species composition and diversity of mangroves in three transects randomly by establishing (10 ×10 m) plots perpendicular from shoreline to inland. At this current stage, the coastal community was not depended on Sibuti mangroves forest in terms of direct benefits, like; energy fuel wood 52 (87%), timber 58 (97%), grasses/fodder leaves 53 (88%), construction pole/material 58 (97%), livestock grazing 48 (80%), wildlife hunting 43 (72%), Medicinal Plants/NWFPs 55 (92%) and thatching material 57 (95%). However, low dependency was recorded on mangrove forest in term of crabs and mollusk collection 33 (55%), Nypa fruits collection 21 (35%) and Nypa leaves collection 19 (32%). Fishing was the only direct benefit, which was highly getting by the community 29 (48%) from Sibuti mangrove forest. The community believed that mangrove forest provide them in-direct benefits such as breeding ground of fish 43 (72%), protecting their land from soil erosion 36 (60%), contributing towards land formation 44 (73%), filtering the water resource 39 (65%), increasing scenic view 43 (72%), providing food to the fish 48 (80%), working as nutrients hub for fishes 45 (75%), wildlife habitat 43 (72%), protection from floods 41 (68%), protection from cyclones/storms/tornados 45 (75%) and protecting them from Tsunami 34 (57%). Interest of paying visit to the forest was casually found in 27 (45%). Majority i.e., 36 (60%) viewed Sibuti mangroves as benefited in terms of eco-tourism. Most of the people i.e., 46 (77%) were always willing to play role in the development of Sibuti mangroves, 40 (67%) interested in learning about conservation and protection practices, while 37 (62%) were ready for volunteer role in conservation and protection if assign to them. Most of them i.e., 36 (60%) were ready play role as volunteer and 46 (77%) was ready to work as facilitator. Majority 32 (53%) were willing to pay donations. The educational, research and training program were welcomed by 58 (98%) of the respondents. The people believed that forestry resource could be managed through community involvement. Similar observation was found for fishery, wildlife and eco-tourism development. Joint forest management approach was supported by 47 (78%) and 35 (58%) were satisfied about government efforts for protection, development and conservation of the forest. Majority i.e., 44 (73%) of the people viewed that Sibuti mangrove forest was not facing human pressure on the resource. Survey on mangrove species composition found that nine true mangroves species were recorded and Rhizophora apiculata was recorded as dominated species. The stand density was recorded as 1938 trees ha-1, 1722 saplings ha-1 and 6222 seedlings ha-1. The average diameter of tree in the stand was 21 cm, 13 m for height and 202 m2 ha-1 for basal area. The average diameter of dominant species (R. apiculata) was 24 cm, height 15 m and basal area 176 m2 ha-1. The Importance Value Index (IVI) of R. apiculata was 202 followed by 64 for Xylocarpus granatum. Shannon diversity indices (H´), Margalef richness (D) and Peilou evenness (J´) were calculated to be 1.18, 1.41 and 0.54, respectively. Similarity of species diversity showed two major clusters for the whole forest stand. The findings of this study suggest that Sibuti mangrove forest was undisturbed and healthy. The people were mostly benefited from indirect uses rather than direct uses and they were well aware of the mangrove forest resources. The forest could be managed and conserved in a better way for multi-sectoral uses like eco-tourism, biodiversity, research and education and community people should be considered as primary stakeholder. Integrated resource management approach should be adopted rather than managing the resource as a wildlife sanctuary only.